Pengaruh Kecerdasan Emosional terhadap Prestasi Belajar Matematika pada Siswa SMP Kelas VIII - Rofyanter Leoh; Kristoforus Djawa Djong; Meryani Lakapu (Asimtot : Jurnal Kependidikan Matematika, 2019)
This study aims to determine the effect of emotional intelligence on the learning achievement of class VIII junior high school. This type of research is quantitative research. The population in this study is all students of class VIII SMP N 2 Kupang and the research sample is class VIII D students with the sampling technique is simple ramdom sampling. Data collection techniques using questionnaires and mathematics learning achievement tests. Data analysis was carried out in two ways, namely the SPSS program. From the results of the analysis, based on the tests of normality, linearity, significance, emotional intelligence has an influence on mathematics learning achievement and was obtained by equation of regression Y = 0,642X and t-count = 4.272 > 2, 052 = t table then, a push H0, it means that there is a significant effect of emotional intelligence on learning achievement. Based on the results of the study, the researcher concluded that there was a significant effect of emotional intelligence on mathematics learning achievement of class VIII students of SMPN 2 Kota Kupang.